PENEGAKAN HUKUM PIDANA PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT YANG TIDAK MEMILIKI IZIN USAHA PERKEBUNAN DI KABUPATEN INDRAGIRI HULU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Plantation crime is a special crime that is governed by criminal provisions. Companies that do not have a plantation business permit will be subject to criminal witnesses, namely those listed in Article 105 of Law Number 39 of 2014 concerning plantations. There are still oil palm plantation companies in Indragiri Hulu Regency that do not have plantation business permits and these oil palm plantation companies are still operating and no criminal witnesses have been given to oil palm companies that do not have plantation business permits. The purpose of writing this thesis, namely:. First, criminal law enforcement against oil palm plantation companies that do not have oil palm plantation business permits that do not have oil palm plantation business permits in Indragiri Hulu District; Second, what are the factors that obstruct the enforcement of criminal laws against oil palm plantation companies that do not have oil palm plantation business permits in Indragiri Hulu District; Third, efforts are made to resolve barriers and law enforcement for oil palm plantation companies that do not have plantation business permits in Indragiri Hulu Regency. This type of research is classified as sociological research, because in this study the author directly conducts research at the location or place to provide a complete and clear picture of the problem under study. This research was conducted at the Indragiri Hulu District Police, the Plantation Service, the One Stop Investment and Integrated Services Service (DPMPTS), the Environmental and Forestry Law Enforcement Agency Section II Sumatra, while the population and samples were all parties related to the problem. In this research, the data source used, primary data and secondary data, and tertiary data, were used to collect data in this study by interviewing and studying literature. . From the results of the research and discussion it can be concluded that, First, the criminal law enforcement of oil palm plantation companies is very weak and needs to be enforced through the implementation of Law Number 39 of 2014 concerning Plantations; secondly, there are no community reports about oil palm plantations that do not have plantation permits, there is no good coordination between the Police and the Plantation Service and the One Stop Investment and Integrated Service Agency which makes the police never take up the case. Keywords: Criminal Law Enforcement-Plantation